AN AN ANALYSIS OF DIFFICULTY ON READING EXERCISES IN ENGLISH TEXT BOOK USED BY THE FIRST YEAR STUDENTS OF SMP NEGERI WINI: - - Ani Siki, Jeli Maria De Fatima; Lasi, Febronia; Bouk, Edmundus (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
The objective of this study was to identify what difficulties are faced by the students with reading exercises, and to what level students find difficulty in reading exercises. In this research, the writer used qualitative research. Miles and Huberman state that qualitative analysis use word that is arranged in the text that is expanded. reading comprehension. subjects of this study are students of class VII SMP N WINI Academic Year 2021/2022 because based on preliminary research there is a tendency that them to have difficulties. The instrument of this research is the assessment of reading comprehension and reading test which is done by reading. This will be used to answer questions from the research, and from severalquestions provided by the writer. The aspects that are the focus of this research are literal reading comprehension and interpretive reading comprehension. The procedure of Data Collections in this research, the writer collected data by using a reading comprehension test and interview as the instrument to collect the data. The technique of Data Analysis Miles and Huberman stated that qualitative analysis uses words arranged in the text. Namely data reduction, data presentation, and conclusion drawing. The writer presents the data from the difficulties in comprehending English reading text the result of the research shows that there are 43,08% of students have difficulties understanding to look for the main idea. Then, there are 16,92% of students have difficulties understanding vocabulary. Then there are 40% of students have difficulties understanding and making inferences.